Analysis of the Sources Relied on by Sirajuddin Al-Ushi in his Work "Al-Fatawa Al-Sirajiya" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The document "Analysis of the sources relied on by Sirajuddin al-Ushi in his work al-Fatawa al-sirajiya" provides an in-depth examination of the diverse range of sources that Sirajuddin al-Ushi references in his compilation of fatwas. It categorizes these sources based on their reliability within the Hanafi school of thought, distinguishing between accepted (maqbul) and rejected (mardud) works, and further subdividing accepted works into categories based on their significance and reliability. This analysis underscores the meticulous approach al-Ushi took in grounding his fatwas in well-regarded Islamic jurisprudential sources.